Harina De AjÃ De RatÃ³n (Capsicum MÃnimum) Como Anticoccidial Natural En Pollos De Engorde, ManabÃ-Ecuador - OÃ±ate, Francisco Javier; Fiallos, Luis; Duchi, Nelson; Villafuerte, Alex; PeÃ±afiel, Isabel; Flores, Ãngel; Morales, Klever (European Scientific Journal, ESJ, 2018)
The use of natural plants for the control and treatment of diseases is an alternative to drugs and antibiotics. In the present test the hot pepper (Capsicum Minimum) was used as an anticoccidial in broiler chickens, it was taken as a reference to salinomycin (control) including 350g / ton, faced with three increasing levels of hot pepper flour (350, 500 and 1000g / ton). For the effect, 160 newborn chicks of the Cobb 500 line were used, distributed in four treatments and four repetitions under a completely randomized design, for the comparison of means the discrete Tukey test (0,05) was used, the data were analysed in the free version of InfoStat 2014 program. The variables analysed were weight, feed consumption, feed conversion, mortality and counting of Eimeria oocysts in faeces. Regarding the weight, the treatments presented statistical equality (p> 0.05), numerically T3 registered the highest (2405.13 Â± 43.33); and food conversion T1 and T2 (1.69), T3 and T4 (1.80) did not present differences between their means. Regarding mortality, T3 did not present deaths, not so, T4 (2.5%); T2 (5%) and T1 (10%); for oocyte count of E. Tenella and Acervulina T3 and T4 do not register eggs, T1 (3000 and 4500) and T2 (2500 and 1500, respectively). The hot pepper flour has anticoccidial activity in broiler chickens, its inclusion did not alter the productive parameters of the flock, which is recommended to be used during the fattening stage of the chickens or fowls.